COMBILOSE: A novel lactose-based co-processed excipient for direct compression - Sandesh Narayan Somnache, Karkala Vasantakumar Pai, Ajeet Madhukar Godbole, Pankaj Sadashiv Gajare, Arti Shashikant Pednekar (Journal of Applied Pharmaceutical Science, 2023)
Lactose is the commonly used diluent in the manufacturing of tablets dosage form. However, the poor flowability and compressibility of lactose limit its use as a directly compressible filler binder. In this research work, composite excipient COMBILOSE was developed as a directly compressible filler binder by coprocessing technique. Lactose monohydrate was co-processed with maltose monohydrate and maize starch by co-freezing and co-drying techniques. Physical blends of lactose monohydrate and maize starch were prepared in the ratio of 20:1. Prepared physical blends were dispersed in 5% w/v, 10% w/v, and 15% w/v aqueous solutions of maltose monohydrate. Dispersions were subjected to co-freezing followed by co-drying. Microfine granules of COMBILOSE were obtained by comminution and sifting of the dried composites. The developed composite excipients were evaluated for various excipient functionalities. The results of studies showed that coprocessing of lactose monohydrate with maize starch and maltose monohydrate can improve flowability and tabletability. COMBILOSE containing 10% w/v of maltose monohydrate showed better dilution potential and reduced lubricant sensitivity. Improvement in compressibility was observed, which could be due to the pre-gelatinization of maize starch during the development process. In conclusion, a blend of lactose monohydrate and maize starch in a ratio of 20:1 when processed with 10% of maltose monohydrate could provide good compressibility and better dilution potential with a reduced lubricant sensitivity.